Politics of Gross National Happiness Governance and Development in Bhutan - Schroeder, Kent (Springer International Publishing, 2018)
This book explores the practices of governance in Bhutan and how they shape the implementation of the country's Gross National Happiness (GNH) development strategy. The author examines whether Bhutan's innovative GNH governance framework successfully navigates competing power dynamics and generates the intended human development outcomes of Gross National Happiness. The analysis is structured around a comparison of the implementation of four GNH development policies - tourism, media, farm roads and human/wildlife conflict - and their larger implications on power, governance and the human development paradigm in Bhutan and beyond. .